From our house a memoir - Martin, Lee 1955- (New York PLUME, 2001)
An American memoir of Lee Martin, born into a farming family the same year his father unexpectedly lost both of his hands. Lee's father, once known for doing a good turn for his neighbors, changed that afternoon in the cornfields to become an embittered, hardened man. -- Jacket.
First Plume Printing, June 2001.
Keywords: Martin, Lee -- 1955- -- Homes and haunts -- Illinois; Martin, Lee -- 1955- -- Childhood and youth; Authors, American -- Homes and haunts -- Illinois; Authors, American -- 20th century -- Biography; Agriculture -- Accidents -- Illinois; Fathers and sons -- Illinois; Rural families -- Illinois; Illinois -- Intellectual life -- 20th century; Illinois -- Social life and customs